LTE-advanced based handover mechanism for natural disaster situations - Ray, SK; Sarkar, NI; Deka, D; Ray, SK (IEEE, 2015)
Telecommunication networks often face power outage problems in the natural disaster affected areas. Also, owing to a sudden substantial increase in network traffic loads the battery backup power of the base stations run out quickly and therefore hampering telecommunication services. To overcome this system performance issues, we propose a Long Term Evolution (LTE)-Advanced (LTE-A)-based user equipment (UE)-controlled and base station (Evolved Node B or eNB)-assisted handover scheme. The idea is to limit the arrival of new traffic to an already overloaded eNB by diverting their handover to lightly loaded nearby eNBs. The novelty of this work is the ability of an UE to self-detect the occurrence of a natural disaster and to self-select the most suitable target eNB (TeNB) to handover with in the disaster affected areas. The handover is performed by obtaining the weighted average score (WAS) of the direction of motion (DoM) and the leftover battery backup power of the different neighboring eNBs (NeNB). The UE also predicts its DoM and dynamically adjust the weights of the two parameters if it’s a disaster situation. Preliminary simulation results show that the scheme can offer up to 65% handover success rate in disaster situations.
Keywords: Natural disaster; Seamless handover; Leftover power; Base station; LTE-A; Weighted average score